An experimental study to evaluate the use of oil to prevent differential stuck pipe in Nahr Umr oil field - Alhisnawy, Karrar Talib; A. Alrazzaq, Ayad A. Alhaleem; Ben Mahmud, Hisham (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Differential pipe sticking (DSP) is a main challenge when using water-based drilling fluids developed with bentonite clay. This study employed a Fann VG meter, a self-fabricated tester, and a stickance tester to examine the effect of oil on water-based drilling mud (WBM) and to control this issue. The study found that oil is more suitable than WBM for the composition of drilling fluids. Empirical investigations showed that adding oil to the drilling fluid maintained its rheological characteristics, reduced filtration loss from 19 to 8 cc, and decreased the friction coefficient from 0.32 to 0.05. The tendency of the drilling fluid to stick was also significantly diminished, indicating its effectiveness in preventing differential stuck pipe issues associated with water-based drilling mud. Additionally, it was observed that oil should be used in high-permeable zones rather than WBM. The Nahr Umr oil field was selected to study the problem of differential stuck using a simple well site test for monitoring and optimizing drilling fluid properties. The study concluded that using emulsion mud as a drilling fluid can prevent and treat differential stuck pipe without any torque, due to its ability to reduce the friction coefficient to less than 0.05. However, it is essential to ensure that the oil percentage does not exceed 3% to avoid any change in the rheological properties.